English Teachers' Strategies in Teaching Reading Comprehension at the Second Grade Students in SMPN 1 Panyabungan Selatan - Nur Hidayah; Ainul Addinna (Journal of English Language Teaching, 2023)
This research aims to analyze the strategies used by English teachers in teaching reading comprehension and how these strategies are implemented. This research uses a qualitative descriptive approach using questionnaires, observations and interviews as research instruments.  This research focuses on two English teachers who teach second grade students at SMPN 1 Panyabungan Selatan.  Findings revealed three main strategies used by teachers: Scaffolding, Think Aloud, and QARS (Question Answer Relationship). Scaffolding strategies help students develop their understanding of the ideas in the text. Think Aloud helps students connect the texts they read to their previous knowledge, allowing them to relate information to the context of the text. QARS allows teachers to assess students' understanding of the material being taught. Apart from that, the use of this strategy is effective because it encourages students to be more active so as to generate ideas and increase their participation in the learning process. It also allows teachers to ensure that students focus on the text and understand its content.